Properties of nematicons in low-birefringent nematic liquid crystals - Kwaśny, Michał; Laudyn, Urszula Anna; Sala, Filip A; Piccardi, Armando; Alberucci, Alessandro; Karpierz, Mirosław A; Assanto, Gaetano (Photonics Letters of Poland, 2013)
We investigate nonlinear self-focusing and nematicon generation in low birefringencenematic liquid crystals (NLCs), where n=0.04. Nematicons are obtained for larger optical powers but they are more than in NLCs with standard birefringence, of the order of n=0.2 Moreover, in low-birefringent NLCs, polarization components exchange energy in a nonlinear regime. Such behaviour is not observed in typical NLCs, where ordinary and extraordinary waves tend to propagate independently due to large walk off.The results of our experimental rest are also compared with numerical simulations, using a fully vectorial BPM. Calculations and experimental results are in good qualitative and quantitative agreement. Full Text: PDF References G. Assanto and M. A. Karpierz, "Nematicons: self-localised beams in nematic liquid crystals", Liq. Cryst. 36, 1161 (2009). CrossRef M. Peccianti and G. Assanto, "Nematicons", Phys. Rep. 516, 147(2012). CrossRef M. Peccianti, G. Assanto, A. De Luca, C. Umeton and I. C. Khoo, "Electrically assisted self-confinement and waveguiding in planar nematic liquid crystal cells", Appl. Phys. Lett. 77, 7 (2000). CrossRef M. A. Karpierz, M. Sierakowski, M. Swillo and T. Wolinski, "Self Focusing in Liquid Crystalline Waveguides", Mol. Cryst. Liq. Cryst. 320, 157 (1998). CrossRef U. A. Laudyn, M. Kwasny, M. A. Karpierz, "Nematicons in chiral nematic liquid crystals", Appl. Phys. Lett. 94, 091110 (2009). CrossRef U. A. Laudyn, M. Kwasny, K. Jaworowicz, K. A. Rutkowska, M. A. Karpierz and G. Assanto, "Properties of spatial solitons in chiral nematic liquid crystal cells", Photon. Lett. Poland 1, 7 (2009). CrossRef I. C. Khoo, "Liquid Crystals, Second Edition", Wiley & Sons, New Jersey (2007). CrossRef A. Piccardi, A. Alberucci, G. Assanto, "Soliton self-deflection via power-dependent walk-off", Appl. Phys. Lett.96, 061105 (2010). CrossRef F. A. Sala and M. A. Karpierz, "Modeling of molecular reorientation and beam propagation in chiral and non-chiral nematic liquid crystals", Opt. Express 20, 13923 (2012). CrossRef A. Piccardi, M. Trotta, M. Kwasny, A. Alberucci, R. Asquini, M. Karpierz, A. D'Alessandro and G. Assanto, "Trends and trade-offs in nematicon propagation", Appl. Phys. B 104, 805 (2011). CrossRef R. Dąbrowski, J. Dziaduszek and T. Szczuciński, "Mesomorphic Characteristics of Some New Homologous Series with the Isothiocyanato Terminal Group", Mol. Cyst. Liq. Cryst. 124, 241 (1985). CrossRef